Emerging trends in strategic planning - David, Fred R.; David, Forest R.; Kovács, Tünde Zita; Nábrádi, András (Applied Studies in Agribusiness and Commerce, 2020)
In today’s rapidly changing world, there is an increased need for excellent strategic planning. A firm’s survival may indeed hinge on the firm’s planning process being exemplary. Various aspects of the strategic planning process are under review today as organizations wrestle to compete more effectively. This paper reveals and describes five emerging trends or tools being utilized today by firms to more effectively engage in strategic planning. Specifically, the emerging trends and tools to be discussed in this paper are as follows: 1) Assure vision and mission statements include desired characteristics 2) Perform SWOT (Strengths-Weaknesses-Opportunities-Threats) analysis using AQCD (Actionable, Quantitative, Comparative, and Divisional) factors 3) Utilize varied sources to obtain AQCD information 4) Utilize QSPM (Quantitative Strategic Planning Matrix) analysis to determine the relative attractiveness of alternative strategies 5) Use excel-based software to facilitate and enhance the strategic planning process. The purpose of this paper is to familiarize readers with basic new tools and techniques being used by organizations to effectively develop an improved strategic plan for the firm. JEL Code: M21, O21